Pengaruh literasi keuangan terhadap pengelolaan keuangan pada pelaku UMKM - Putri S, Tasya Aprilianti; Hidayaty, Dwi Epty; Rosmawati, Ery (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study aims to determine the effect of financial literacy on financial management of MSME actors located in Purwasari District, Karawang Regency. This research is a quantitative descriptive study with data obtained from the answers to questionnaires about financial literacy and financial management answered by MSME owners. There are 1,749 MSMEs in Purwasari District, Karawang Regency as the population in this study with the appropriate data source from the karawangkab.go.id website. So that obtained 95 MSME business actors in Purawasari District, Karawang Regency which were used as samples in this study. In this study, multiple linear regression analysis will be carried out regarding the primary data obtained by probability sampling technique using the simple random sampling method. In this study, a SPSS 26 calculation tool is needed. Based on the results of this study, it can be concluded that the financial management of MSMEs in Purwasari District, Karawang Regency is significantly influenced by financial literacy variables, namely basic knowledge of finance, savings and credit, investment, and insurance simultaneously.